P2_5 The Apparent Magnitude of Î± Orionis Supernova - West, Andrew; McHugh, Melissa; Blake, James; Hall, Rosanna Carol (Physics Special Topics, 2011)
The star Î± Orionis (Betelgeuse) is to become a type II supernova at the end of its life. Some have postulated that this supernova will be bright enough that it will be visible during the day. Betelgeuse will have an apparent magnitude of around -8.7, brighter than Venus, which can be seen when the sun is low in the sky. The star Î± Orionis will be most probably be visible throughout the day when it reaches the final stages of its evolution.